Requirements for Transparency and Communicability of Regulatory Science - A. Alan Moghissi; Richard A. Calderone; Camille Estupigan; Rae Koch; Kelsey Manfredi; Vanessa Vanderdys (SAGE Publishing, 2018)
This article presents the results of a study attempting to provide examples that implement transparency and communicability elements of Ethical Rules Principle of Best Available Regulatory Science (BARS) and Metrics for Evaluation of Regulatory Science Claims (MERSC). It starts with an overview of regulatory science and briefly summarizes principles of BARS and key pillars of MERSC. Subsequently, the BARS/MERSC system is used to evaluate the linear nonthreshold (LNT) process used in cancer assessments and the similar process used for evaluating in particulate matter (PM) exposure. The study identifies 3 parts in dose-response curves, where the first part is reproducible science and the second part includes uncertainties and often requires the application of precautionary principle. The primary reason for disagreements on LNT and PM is a lack of recognition that the third part is based on desire of regulators to be protective, a policy decision process. Two PM epidemiological examples are included in this study to demonstrate the point. The regulatory process would benefit from recognizing the distinction between science and policy and excluding policy from regulatory science. Furthermore, the society would greatly benefit from increased transparency in the regulatory process and compliance with the Jeffersonian communication principle